(untitled) (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2018)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a highly prevalent and concerning disorder in the classroom (Bekle, 2004). Teachers need to provide supports for these students, yet it is often the case that they lack sufficient knowledge to do so (e.g., Alkahanti, 2013). This paper provides a review of recent literature (2004 to the present) regarding teacher knowledge of ADHD in English-speaking countries. This includes a discussion of overall themes, areas of knowledge and misunderstanding, with emphasis on the need to ensure that teachers have basic knowledge of the etiology, symptoms, and treatments of ADHD. Accurate ADHD knowledge and ongoing professional development would likely benefit schools and communities.